PENGARUH PEMBERIAN EDUKASI PENANGANAN GAWAT DARURAT TERSEDAK PADA ANAK MENGGUNAKAN TEKNIK HEIMLICH MANEUVER TERHADAP PENGETAHUAN IBU DI TAAM ASYIMA NUSANTARA TAHUN 2025 - IP, Ananda; Budi, Rustandi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Choking is an emergency that often occurs in children, especially in preschool or toddler age children, and can be fatal if not treated promptly. The Heimlich Maneuver technique is one of the effective methods in dealing with choking but is not recommended for children less than 1 year old, but there are still many mothers who do not have the knowledge and skills to perform this technique. Therefore, education is needed to improve mothers' understanding of choking emergency management. Research Objectives: This study aims to determine the effect of providing education on the Heimlich Maneuver technique on mothers' knowledge in handling choking emergencies in preschool children at TAAM Asyima Nusantara. Research Methods: This study used a pre-experimental pretest posttest one group design. Where the level of knowledge of mothers was measured before and after education was given. Education was provided using a lecture method with demonstrations with powerpoint slides and puppets. The sampling technique used total sampling of 10 respondents for preliminary studies and 32 respondents for research. Data were analyzed using the Wilcoxon test. Results: The study showed that before being given education, (81.3%) of respondents had a poor level of knowledge. After being given education, there was a significant increase in the level of maternal knowledge (87.5%) of respondents reached good category knowledge (p-value <0.001). Conclusion: There is an effect of education on the provision of emergency handling of choking in children using the Heimlich Maneuver technique on maternal knowledge at TAAM Asyima Nusantara